Peran Human Capital Dan Teknologi Informasi Pada Organizational Performance Dalam Persiapan Presidensi G20 - I Gusti Ayu Kade Indah Dewi (CV ODIS, 2022)
This study aims to test and analyze the role of human capital and information technology in organizational performance in preparation for the G20 presidency. This research was conducted on Dinas Pariwisata Provinsi Bali with a total of 118 employees. Sampling in this study used the Slovin formula to determine the sample amount that could represent and describe the characteristics of the entire population and obtained 54 samples. In this study, data collection techniques were used with the interview, observation, and questionnaire methods. The data analysis techniques used in this study are multiple linear regression analysis, F test, and t-test. The results of this study indicate that (1) human capital has a positive and partially significant effect on organizational performance in preparation for the G20 presidency. (2) Information technology has a positive and partially significant effect on Organizational performance in preparation for the G20 presidency. (3) Human capital and information technology have a significant simultaneous effect on Organizational performance in preparation for the G20 presidency.